PERAN PEREMPUAN DI ERA DIGITAL: SEBUAH ANALISIS WACANA FEMINIS MODEL SARA MILLS - Teti Sobari; Rida Khamilawati (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2021)
Abstract: All women stereotypes in many ways contain injustices. It turns into a culture that develops in the community, making it difficult for women to get out from all the labels that are attached. Starting from this culture, then there emerged several schools of feminism to fight for women's rights which were confined in that injustice. The purpose of this study is to know women's image in the text and the position of the actor in the text. The method employed is qualitative descriptive with a critical discourse analysis to the text